Effects of Occupational Health Prevention Program among Thai Farmers - Rattanaselanon, Peerayut; Sanprakhon, Panawat; Lormphongs, Srirat; Chanvaivit, Sirirat (Journal of Food Health and Bioenvironmental Science, 2018)
The problem of inappropriate chlorpyrifos usage is an important concern for workers who have direct exposure. The purpose of the study was to evaluate the effectiveness of occupational health prevention program among Thai farmers, using a quasi-experimental design with the two-groups: pre-test-post-test. The samples consisted of 70 farmers who had mixed or sprayed CPF and used CPF spray for more than a year and had unsafe blood cholinesterase enzyme level. 35 subjects in each group were equally assigned by random assignment to an experimental group and a control group, and both groups had no difference in the characteristics. Those in the experimental group received the occupational health prevention program at week 1, but those in the control group received the usual care. Outcomes were measured before intervention (baseline), and at 1 and 4 weeks after intervention, and then data were analyzed with descriptive and using repeated measures of ANOVA testing. The findings reveal that participants in the intervention group had improved self- protective behavior and blood cholinesterase enzymes, and had lower symptoms. They have differed from the control group with statistical significance (p<0.001). Thus, this program should be considered for implementation to improve the safe use of Chlorpyrifos.